The Mythologema of the Tree of Life in the Context of Artistic Time (Grant Matevosyan, Viktor Astafyev) - Petrosyan, David (Bulletin of Yerevan University B: Philology, 2024)
The Tree of Life is one of the important symbols of human existence and immortality. It also receives its unique expression in artistic literature when we study this issue from the perspective of artistic time. In particular, in several works of Grant Matevosyan and Viktor Astafyev, the real image of the tree is transformed into a mythological structure, the presence of which has a direct impact on the internal symbolic connections of the artistic environment and heroes, plot, fabula, and action. During the research, we took as a basis the concept of spiritual time proposed by Augustine the Blessed, as a model of artistic time, where the three transformations of the present (past present, present present, present future) in the stories of Matevosyan and Astafyev lead to interesting discoveries. In particular, Matevosyan creates history and the fate of his nation using the Tree of Life in some of his works. Meanwhile, Astafyev emphasizes the imperative of staying true to the power of the Tree of Life based on the opposition of foreign and native elements. In another temporal segment (present present), the image of the tree is woven into the creative structure of the writer and becomes a process of creating a myth of the Tree of Life, giving the text new branches of the mythologema of the Tree. In this context, the interconnections of the mythologema of the Tree of Life and artistic time reveal new possibilities for creative freedom in the works of G. Matevosyan and V. Astafyev.